Phylogeny of Porphyromonas gingivalis by Ribosomal Intergenic Spacer Region Analysis - Rumpf, Robert W. (American Society for Microbiology, 2000)
Periodontitis has been associated with the presence of Porphyromonas gingivalis, and previous studies have shown phenotypic differences in the pathogenicities of strains of P. gingivalis. An accurate and comprehensive phylogeny of strains of P. gingivalis would be useful in determining if there is an evolutionary basis to pathogenicity in this species. Previous phylogenies of P. gingivalis strains based on random amplified polymorphic DNA (RAPD) analysis and multilocus enzyme electrophoresis (MLEE) show little agreement. While the 16S ribosomal gene is the standard for phylogenetic reconstruction among bacterial species, it is insufficiently variable for this purpose. In the present study, the phylogeny of P. gingivalis was constructed on the basis of the sequence of the most variable region of the ribosomal operon, the intergenic spacer region (ISR). Heteroduplex analysis of the ISR has been used to study the variability of P. gingivalis strains in periodontitis. In the present study, typing by heteroduplex analysis was compared to ISR sequence-based phylogeny and close agreement was observed. The two strains of P. gingivalis whose heteroduplex types are strongly associated with periodontitis were found to be closely related and were well separated from strains whose heteroduplex types are less strongly associated with disease, suggesting a relationship between pathogenicity and phylogeny.